scRNA-seq analysis of cells comprising the amphioxus notochord - Takahashi, Hiroki; Hisata, Kanako; Iguchi, Rin; Kikuchi, Sakura; Ogasawara, Michio; Satoh, Noriyuki (Developmental biology, 2024)
Cephalochordates occupy a key phylogenetic position for deciphering the origin and evolution of chordates, since they diverged earlier than urochordates and vertebrates. The notochord is the most prominent feature of chordates. The amphioxus notochord features coin-shaped cells bearing myofibrils. Notochord-derived hedgehog signaling contributes to patterning of the dorsal nerve cord, as in vertebrates. However, properties of constituent notochord cells remain unknown at the single-cell level. We examined these properties using Iso-seq analysis, single-cell RNA-seq analysis, and in situ hybridization (ISH). Gene expression profiles broadly categorize notochordal cells into myofibrillar cells and non-myofibrillar cells. Myofibrillar cells occupy most of the central portion of the notochord, and some cells extend the notochordal horn to both sides of the ventral nerve cord. Some notochord myofibrillar genes are not expressed in myotomes, suggesting an occurrence of myofibrillar genes that are preferentially expressed in notochord. On the other hand, non-myofibrillar cells contain dorsal, lateral, and ventral Müller cells, and all three express both hedgehog and Brachyury. This was confirmed by ISH, although expression of hedgehog in ventral Müller cells was minimal. In addition, dorsal Müller cells express neural transmission-related genes, suggesting an interaction with nerve cord. Lateral Müller cells express hedgehog and other signaling-related genes, suggesting an interaction with myotomes positioned lateral to the notochord. Ventral Müller cells also expressed genes for FGF- and EGF-related signaling, which may be associated with development of endoderm, ventral to the notochord. Lateral Müller cells were intermediate between dorsal/ventral Müller cells. Since vertebrate notochord contributes to patterning and differentiation of ectoderm (nerve cord), mesoderm (somite), and endoderm, this investigation provides evidence that an ancestral or original form of vertebrate notochord is present in extant cephalochordates. Constituent cells of the amphioxus notochord with gene expression. (A) A transverse section of the middle-part of the body showing the notochord (not) at the mid-dorsal line, which is sandwiched by the dorsal-side nerve cord (nc) and the ventral-side pharynx (ph). Note that Brachyury (blue) is expressed in the notochord and in the hepatic cecum (hc), hedgehog (green) in the notochord and in the endostyle (en), and MRLC (myosin regulatory light chain, brown) in the central region of the notochord and body-wall muscle (bwm), but not in muscle (mus). (B) Notochord expression of Brachyury (blue), hedgehog (green), and MRLC (brown). M, Müller cells; DM, dorsal Müller cells; LM, lateral Müller cells; VM, ventral Müller cells; MC, myofibrillar cells. DM and LM express both Brachyury and hedgehog, while VM express low level of hedgehog (broken circle). (C) An image of a serially transverse-sectioned notochord showing the complex arrangement of its constituent cells with expression of the foregoing genes gene. gd, gonad; nh, notochordal horn; v, vacuoles. [Display omitted] •Notochord of adult amphioxus was examined by scRNA-seq.•The notochord is composed of myofibrillar and non-myofibrillar cells.•Some non-myofibrillar cells express Brachyury and hedgehog.•These correspond to Müller cells and likely interact with nerve cord or somites.•Amphioxus notochord has ancestral properties of vertebrate notochord.